A search for correlations of TeV gamma rays with ultra-high-energy cosmic rays - Akerlof, C; Biller, S; Boyle, P; Buckley, J; Carter-Lewis, D; Catanese, M; Cawley, M; Connaughton, V; Fegan, D; Finley, J; Gaidos, J; Hillas, A; et al. (Institute of Physics Publishing, 2003)
A search was conducted for TeV γ-rays emitted from the direction of the ultra-high-energy cosmic ray detected by the Fly's Eye experiment with energy E ∼ 3 × 1020 eV. No enhancement was found at a level of 10-10 cm-2 s-1 for E > 350 GeV. A steady source of ultra-high-energy cosmic ray protons or photons would be expected to produce a γ-ray flux above this level. An upper limit was also set for the flux of TeV γ-rays from 3C 147, the most prominent active galactic nucleus in the error box.